2010
DOI: 10.1186/1748-717x-5-46
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Epidermal Growth Factor Receptor (EGFR) expression in human meningioma

Abstract: PurposeThis study explores whether meningioma expresses epidermal growth factor receptor (EGFR) and determines if there is a correlation between the WHO grade of this tumor and the degree of EGFR expression.MethodsFollowing institutional review board approval, 113 meningioma specimens from 89 patients were chosen. Of these, 85 were used for final analysis. After a blinded review, immunohistochemical stains for EGFR were performed. Staining intensity (SI) was scored on a scale 0-3 (from no staining to strong st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 37 publications
3
43
0
Order By: Relevance
“…Elevated levels of EGFR observed in every meningioma in the present study, is consistent with that demonstrated in a large cohort of meningiomas in which the highest degree of its expression was in benign meningiomas. In addition, they compared immunohistochemistry results to malignant meningiomas, concluding that the expression is inversely correlated to tumour grade and may serve as a potential therapeutic target with selective EGFR inhibitors (39).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of EGFR observed in every meningioma in the present study, is consistent with that demonstrated in a large cohort of meningiomas in which the highest degree of its expression was in benign meningiomas. In addition, they compared immunohistochemistry results to malignant meningiomas, concluding that the expression is inversely correlated to tumour grade and may serve as a potential therapeutic target with selective EGFR inhibitors (39).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 60% of grade II meningiomas have shown point mutations (mainly deletions) in chromosomes [18]. Furthermore, 75%-90% of grade III meningiomas have similar point mutations in chromosomes [18].…”
Section: Molecular Genetics Of Grade Ii/iii Meningioma (Atypical/anapmentioning
confidence: 99%
“…Furthermore, 75%-90% of grade III meningiomas have similar point mutations in chromosomes [18]. Mutations in the 1p and 14q regions of the chromosome (where tumor suppressor genes are believed to e housed) are associated with a worse prognosis.…”
Section: Molecular Genetics Of Grade Ii/iii Meningioma (Atypical/anapmentioning
confidence: 99%
“…LRIG1, located at chromosome 3p14.3 [12], encodes a negative feedback regulator of epidermal growth factor receptor (EGFR) signaling [13] that enhances receptor ubiquitination and degradation rates and inhibits signaling [15][16][17]. EGFR is commonly expressed in meningiomas [18][19][20]. LRIG1 has been suggested to be a tumor suppressor gene, and its expression has been linked with a good prognosis and better patient survival in epithelial cancers [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%